Sosialisasi Serta Pembagian Masker Sebagai Langkah Pencegahan Lonjakan Kasus Covid 19 di Pasar Tradisional - Gusti Agung Sri Guntari (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Abstract: Covid-19 or better known as the Corona Virus has become a public concern since its appearance was detected in China for the first time in early 2020. The death of thousands of people due to this virus has made it the center of attention of many countries, including Indonesia. The COVID-19 pandemic has proven to have put pressure on economic and social conditions in Indonesia since the end of 2019. Traditional markets have become places where many people from various places gather, resulting in an increased risk of infection. The risk of infection is not only for traders, but also for buyers and their families and people they meet or have close contact with, so it is very necessary to implement health protocols by market traders.